Influence of aspirin and non-aspirin NSAID use on ovarian and endometrial cancer: Summary of epidemiologic evidence of cancer risk and prognosis. (June 2017) - Verdoodt, F.; Kjaer, S.K.; Friis, S.
Highlights: Observational studies indicate modest reductions in risk of ovarian and endometrial cancer associated with aspirin use. The strongest inverse associations have been reported for long-term consistent aspirin use. Evidence of NSAID use and mortality of ovarian or endometrial cancer is sparse, and the results are mixed. Additional studies of aspirin and non-aspirin NSAID use and ovarian and endometrial cancer risk or prognosisare warranted, focusing on risk variation by usage patterns and user characteristics. Future studies should aim at identifying women who may experience largest benefit of NSAID use on risk or prognosis of gynecological and other cancer types. Abstract: Increasing evidence supports a role for aspirin use in reducing the incidence and mortality of several cancer types. This has spurred a new wave of interest in this widely used drug. In this review, we present and evaluate the epidemiologic evidence of the association between the use of aspirin and other non-steroidal anti-inflammatory drugs (NSAIDs) and the incidence and prognosis of ovarian and endometrial cancer. The evidence of a preventive effect of NSAID use on risk of ovarian or endometrial cancer is based primarily on results from observational studies and, consequently, is only suggestive. Overall, observational studies indicate modest reductions in risk of ovarian and endometrial cancer with aspirin use, whereas the results for non-aspirin NSAID use are equivocal. The strongest inverse associations have been reported for long-term consistent aspirin use, notably among subgroups of users (e.g., those with high body mass index). Few studies have evaluated the influence of NSAID use on the mortality of ovarian or endometrial cancer, and substantial heterogeneity of study characteristics and results preclude any conclusions. Additional studies of aspirin and non-aspirin NSAID use and ovarian or endometrial cancer risk and prognosis are warranted. In the present review, we discuss the importance of comprehensive exposure definitions (i.e., duration, timing, consistency and intensity/dose) and evaluation of potential effect modification according to user characteristics, with the aim of identifying women who may experience the largest benefit of aspirin or non-aspirin NSAID use on risk or prognosis of ovarian and endometrial cancer.